Generation of cell suspensions of East African highland bananas through scalps - Sadik, K.; Rubaihayo, P.R.; Magambo, M.; Pillay, M. (2007)
The improvement of East African highland bananas (EAHBs) using conventional breeding methods is difficult due to their biology and therefore focus on improving them has shifted to exploring methods for establishment of embryogenic cell suspensions, which can then be targeted, for genetic transformation. Shoots of four cultivars namely ‘Musakala’, ‘Kibuzi’, ‘Mbwazirume’ and ‘Lwadungu’ were transferred to a multiplication media modified by adding a combination of N6-benzylaminopurine (BAP) and thidiazuron (TDZ) at concentrations of 24.8/0.45, 16.2/1.14, 14.4/3.50, 12.4/4.55, 10/5.68 mM for scalp generation. These media are referred to as M1, M2, M3, M4 and M5, respectively. Two other treatments designated as M6 and M7 with concentrations of 10 mM TDZ and 100 mM BAP, respectively were included for comparison purposes. The scalps developed were excised and inoculated into liquid induction medium supplemented with either BAP or Zeatin to generate cell suspensions. Scalp formation was achieved earlier and at much lower concentrations of combined BAP and TDZ than when singly applied. Combinations of 12.4/4.55 and 10/5.68 M BAP/TDZ produced the best scalps. The structure of the cell suspension and the rate of cell growth were found to be dependent on the cultivar regardless of the hormone treatment in the induction medium. Cultivars ‘Musakala’, ‘Kibuzi’ and ‘Mbwazime’ produced cell culture of clustered and aggregated cells and high cell numbers, which are a prerequisite for embryo cells development.